School Head’s Conflict Resolution Skills, Organizational School Climate, and Teacher Work Engagement in The New Normal: An Input to Principal and Teacher Development Program - Raymond D. Gomez; Alberto D. Yazon; Lerma P. Buenvinida; Consorcia S. Tan; Marcial M. Bandoy (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2022)
This study determined the school head's conflict resolution skills, organizational school climate, and teachers' work engagement among public school principals and teachers in the City Schools Division in Laguna for the school year 2020-2021. One hundred twelve (112) public school principals and one thousand forty-eight (1048) teachers were the respondents of the study. The researchers utilized a descriptive correlation study design. It made use of adopted and modified questionnaires to assess and measure the variables studied. The statistical tools used to analyze the data gathered were: Mean, standard deviation, Pearson r, and Multiple Linear Regression Analysis. Findings revealed that conflict resolution skills and organizational school climate were relevant to teachers' work engagement. The results were used to determine the principal and teachers’ development program to be proposed to the School Divisions officials. The teachers' work engagement was related to the school heads' conflict resolution skills and organizational school climate. To ensure a more efficient teachers work engagement, school heads are encouraged to continue cultivating a culture of excellence in the school by exposing the teachers to relevant activities that may sustain the work engagement by means of exhibiting quality performance in teaching and learning. Also, supervisors should strengthen the performance of the teachers by providing the technical assistance needed to further improve their performance. Technical assistance should focus on curriculum delivery and the school's operation and management. Keywords:   Conflict Resolution Skills; Development Program; New Normal; Organizational School Climate; Teacher Work Engagement.